A novel homozygous splice site variant in ARL2BP causes a syndromic autosomal recessive rod-cone dystrophy with situs inversus, asthenozoospermia, unilateral renal agenesis and microcysts - Giorgio Placidi; Elena D'Agostino; Paolo Enrico Maltese; Maria Cristina Savastano; Gloria Gambini; Stanislao Rizzo; Gabriele Bonetti; Matteo Bertelli; Pietro Chiurazzi; Benedetto Falsini (BMC, 2024)
Abstract Background This report presents a clinical case of syndromic rod-cone dystrophy due to a splice site variant in the ARL2BP gene causing situs inversus, asthenozoospermia, unilateral renal agenesis and microcysts. The presence of renal agenesis and cryptorchidism expands the clinical manifestations due to ARL2BP variants. The detailed, long-term follow-up contributes valuable insights into disease progression, aiding clinical diagnosis and patient management. Case Presentation The male patient complained of photophobia as the first symptom when he was 20 years old followed by nyctalopia, loss of central visual acuity and peripheral visual field ten years later. Genetic analysis identified a likely pathogenic homozygous variant (c.294-1G > C) involving the splicing acceptor site of intron 4. Reported symptoms together with full-field stimulus threshold testing, electroretinogram and advanced multimodal imaging allowed us to recognize the typical characteristics of a mixed retinal dystrophy. Despite the end-stage retinal disease, this patient still retained a useful residual vision at 63 years and had a slow disease progression during the last 5 years of evaluation. Discussion and conclusions Our findings underscore the variable clinical presentation of ARL2BP variants, emphasizing the importance of a nuanced approach in diagnosing and managing patients. The presence of renal cysts warrants consideration of a differential diagnosis, particularly with Senior-Loken (SLS), Bardet-Biedl (BBS) and Joubert syndromes (JS) but also with Short Rib Thoracic Dysplasia 9, highlighting the need for careful phenotypic evaluation in these cases.